Production of lignosulfonate in NSSC‐based biorefinery. (19th August 2015) - Tarasov, Dmitry; Leitch, Mathew; Fatehi, Pedram
Abstract : The spent liquor (SL) of a neutral sulfite semichemical (NSSC) pulping process contains a considerable amount of lignocelluloses and is treated in wastewater systems. The lignocelluloses, however, can be used for producing value‐added products if they are isolated from the SL. In this article, solvent treatment (mixing acetone, ethanol, or isopropyl with SL) was used as a method for isolating lignosulfonate from SL. The maximum lignosulfonate removal was obtained via mixing isopropyl alcohol with SL at the weight ratio of 20/80, room temperature, and 5.7 pH. The results also showed that the molecular weight and anionic charge density of the precipitates were in the range of 5, 000–70, 000 g/mol and 0.2–1.8 meq/g, respectively. Based on these results, a process was proposed for isolating lignosulfonate from SL and converting the NSSC process to an NSSC‐based biorefinery. © 2015 American Institute of Chemical Engineers Biotechnol. Prog., 31:1508–1514, 2015